2021
DOI: 10.1001/jamanetworkopen.2021.41328
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Colchicine vs Usual Care Alone on Intubation and 28-Day Mortality in Patients Hospitalized With COVID-19

Abstract: IMPORTANCEHospitalized patients with COVID-19 pneumonia have high rates of morbidity and mortality. OBJECTIVE To assess the efficacy of colchicine in hospitalized patients with COVID-19 pneumonia. DESIGN, SETTING, AND PARTICIPANTS The Estudios Clínicos Latino América (ECLA) Population Health Research Institute (PHRI) COLCOVID trial was a multicenter, open-label, randomized clinical trial performed from April 17, 2020, to March 28, 2021, in adults with confirmed or suspected SARS-CoV-2 infection followed for up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…There were 12 studies comprising of 6953 patients included in this meta-analysis [ 10 , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ] [ Fig. 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 12 studies comprising of 6953 patients included in this meta-analysis [ 10 , 11 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ] [ Fig. 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the colchicine arm of the RECOVERY trial, a large randomized clinical trial, found no clinical benefit. Moreover, colchicine showed no beneficial effect on the need of mechanical ventilation or 28-day mortality in a recent randomized clinical trial including 1279 patients hospitalized with COVID-19 pneumonia 21 . Nevertheless, none of these previous studies focused on patients with COVID-19 pneumonia and established hyperinflammation, a subset of patients particularly attractive to assess the effect of colchicine.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, in the scenario of SARS-CoV-2 infection, overweight and obesity are associated with a higher risk of hospital admission 22 and progression to severe COVID 23 . However, since the RECOVERY and ECLA PHRI COLCOVID trials did not collect BMI information 12 , 21 , this is the first clinical trial analyzing the effect of colchicine on overweight patients. Remarkably, the excess of macronutrients in the adipose tissues predisposes to the releases of inflammatory mediators which participate in the cytokine storm aggravating COVID-19 2 .…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, controlled phase II/III trial in hospitalized COVID-19 patients indicated that colchicine could not reduce mechanical ventilation requirement, length of hospital stay, and 28-day mortality (NCT04381936), 165 in line with results of another clinical trial (NCT04328480). 166 Thus, the efficacies of colchicine by the single or combined treatment should be further studied.…”
Section: Pyroptosis and Sars-cov-2mentioning
confidence: 99%